2012
DOI: 10.1371/journal.pone.0046032
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Interactions between Carbohydrate and Protein Quantified by Combination of Theoretical and Experimental Methods

Abstract: Carbohydrate – receptor interactions are an integral part of biological events. They play an important role in many cellular processes, such as cell-cell adhesion, cell differentiation and in-cell signaling. Carbohydrates can interact with a receptor by using several types of intermolecular interactions. One of the most important is the interaction of a carbohydrate's apolar part with aromatic amino acid residues, known as dispersion interaction or CH/π interaction. In the study presented here, we attempted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 60 publications
5
64
0
Order By: Relevance
“…Most importantly, these interactions display a range of binding energies in nature, including those equivalent to the strength of nucleobaseamino acid π-π contacts (up to −70 kJ mol −1 ) (Wilson et al, 2014). This was the first evidence that DNAprotein sugar-π contacts can be stronger than reported for carbohydrate-π interactions (Spiwok et al, 2004(Spiwok et al, , 2006Sujatha, Sasidhar, & Balaji, 2004;Wimmerová et al, 2012).…”
Section: Introductionmentioning
confidence: 79%
“…Most importantly, these interactions display a range of binding energies in nature, including those equivalent to the strength of nucleobaseamino acid π-π contacts (up to −70 kJ mol −1 ) (Wilson et al, 2014). This was the first evidence that DNAprotein sugar-π contacts can be stronger than reported for carbohydrate-π interactions (Spiwok et al, 2004(Spiwok et al, , 2006Sujatha, Sasidhar, & Balaji, 2004;Wimmerová et al, 2012).…”
Section: Introductionmentioning
confidence: 79%
“…The particular localization of one tryptophan residue excludes the low energy conformation of Lewis oligosaccharide from the binding site. The strong stacking interaction that fucose establishes with this tryptophan residue in the binding site of RSL, a lectin closely related to BambL, was recently quantified [57]. Solving the crystal structure of BambL/Lewis x complex demonstrated that indeed, the fucose is bound with stacking to Trp, but that either the adjacent glycosidic linkages or the GlcNAc ring are distorted in order to adjust.…”
Section: Discussionmentioning
confidence: 99%
“…38 For example, atomic partial charges in the ligand or the binding site may vary from those assigned by the utilized force field due to polarization or charge transfer – the effect that is frequently observed with enzymes and metalloproteins. 39 Halogen bonds, CH-π, 40,41 π-π and cation-π interactions are usually not accounted for at sufficient accuracy. In some configurations, London dispersion forces may not be properly approximated by the widely used potentials.…”
Section: Prediction Methods Inaccuracies Vs Input Data Inaccuraciesmentioning
confidence: 99%